2018
DOI: 10.1002/ldr.3105
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon and nitrogen stocks and physical properties under no‐till and conventional tillage cotton‐based systems in the Brazilian Cerrado

Abstract: The aim of this study was to investigate soil C and N stocks and soil physical properties under a cotton (Gossypium hirsutum) based system using no‐till (NT) and conventional tillage (CT). The experiment was established as a randomized block design with four replications of six treatments as follows: [NT1], NT system with crop rotation of cotton/soybean (Glycine max)/maize (Zea mays) + brachiaria (Brachiaria ruziziensis); [NT2], NT system with crop rotation of soybean/maize + brachiaria/cotton; [NT3], NT syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…These results were consistent with those of previous studies in which lower BD values in the upper soil layers were attributed to greater SOC contents and greater root density in the tillage layer as well as greater soil microorganism abundance (De Vos, Van Meirvenne, Quataert, Deckers, & Muys, ; Han et al, ). Significantly lower BDs were observed in the GW and G systems than in the M and GM systems, which was probably attributed to the absence of annual tillage and the input of low‐quality litter (Souza et al, ). In contrast, the GW and W systems received regular tillage, and large amounts of wheat stubble and root as well as the higher stand density of the G system will benefit the litter input (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with those of previous studies in which lower BD values in the upper soil layers were attributed to greater SOC contents and greater root density in the tillage layer as well as greater soil microorganism abundance (De Vos, Van Meirvenne, Quataert, Deckers, & Muys, ; Han et al, ). Significantly lower BDs were observed in the GW and G systems than in the M and GM systems, which was probably attributed to the absence of annual tillage and the input of low‐quality litter (Souza et al, ). In contrast, the GW and W systems received regular tillage, and large amounts of wheat stubble and root as well as the higher stand density of the G system will benefit the litter input (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such intensive tillage practices have led to the acceleration of soil degradation (Asmamaw, 2017). Conservation agriculture, including minimal tillage, the use of surface residue covers and crop rotation, has received wide attention globally and is believed to improve soil functions (Campos Souza et al, 2018). A study on fine-silty Udic Haplustolls (USDA classification) showed that no tillage (NT) resulted in lower soil bulk density and improved soil aggregation, soil organic carbon (SOC) and the total N (TN) content, at 0-15 cm depth, at the harvest stages of a maize-soybean rotation system (Alhameid, Ibrahim, Kumar, Sexton, & Schumacher, 2017).…”
mentioning
confidence: 99%
“…However, in the superficial layers (0 -100 mm), the systems with higher soil mobilization (CC and MC) had lower MRP values when compared to NT. Values below 2000 KPa, providing a favorable condition for root development, according to [24], when they affirm that in CC systems, where the surface layer of the soil is periodically revolved, it is common to observe the momentary increase of the macroporosity values, possible reason why areas submitted to the CC have smaller values of MRP in the superficial layer of the soil.…”
Section: Resultsmentioning
confidence: 94%